Socioeconomic Factors Influencing Cocoa Consumption in Amazonas - Omer Cruz Caro; Edinson Cueva Vega; Yecenia del Carmen Maicelo Rubio; Einstein Sánchez Bardales; Judith Nathaly Alva Tuesta; Alex Javier Sánchez Pantaleón; Cleyton Francisco Chavez Cruz (Qubahan Academic Journal)
Cocoa, a key ingredient in chocolate production, represents a significant crop in the Amazon region, mostly for export. This study examines the socio-economic factors that influence local cocoa consumption. Using a non-experimental explanatory correlational design and a sample of 505 respondents, data were analyzed using descriptive statistics and a binary logistic regression model. The results indicate that age is the only significant factor influencing cocoa consumption (p-value = 0.045), while other variables such as income, educational level, and occupation did not show statistical significance. This work highlights the importance of understanding consumption patterns in cocoa-producing regions, which could inform local market strategies and policies. This study fills a gap in the literature by addressing the factors that impact consumption in a key cocoa-producing region in Peru.